On the dynamical stress field in the pre-stretched bilayered strip resting on the rigid foundation - Guler, Coskun; Akbarov, Surkay D. (SPRINGER, 2007)
The forced vibration of the bi-layered pre-stretching slab resting on the rigid foundatian is investigated within the framework of the piecewise homogeneous bodies model by the use of the equations Three-dimensional Linearized Theory of Elastic Waves in Initially stressed Bodies (TLTEWISB).
Keywords: pre-stretched bilayered strip; rigid foundation; HALF-PLANE; PRESTRETCHED LAYER; Engineering; Mechanics